2023
DOI: 10.3389/fcell.2023.1067861
|View full text |Cite
|
Sign up to set email alerts
|

ROS production in response to high-power microwave pulses induces p53 activation and DNA damage in brain cells: Radiosensitivity and biological dosimetry evaluation

Abstract: Background: Pulsed high-power microwave (HPM) has many applications and is constantly being researched to expand its uses in the future. As the number of applications grows, the biological effects and safety level of pulsed HPM become a serious issue, requiring further research.Objective: The brain is regarded as the most vulnerable organ to radiation, raising concerns about determining an acceptable level of exposure. The effect of nanosecond pulses and the mechanisms underlying HPM on the brain has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The Alamar blue assay for measuring cell cytotoxicity was performed at two different duty ratios of 10% and 36%, and the results were shown in Figure 9 . The U87-MG cell line is the most well known, and it is utilized to study brain cancers [ 41 ]. The viability of the U87-MG with a 10% duty ratio was shown in Figure 9 a–d for treatment times of PTM that were 1, 3, 5, and 7 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Alamar blue assay for measuring cell cytotoxicity was performed at two different duty ratios of 10% and 36%, and the results were shown in Figure 9 . The U87-MG cell line is the most well known, and it is utilized to study brain cancers [ 41 ]. The viability of the U87-MG with a 10% duty ratio was shown in Figure 9 a–d for treatment times of PTM that were 1, 3, 5, and 7 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Despite advances, resistance to conventional therapies, relapses and poor prognosis are very frequent. Innovative anti-cancer strategies, including nanosecond microwave pulses, have been applied to inhibit other types of cancer [ 141 ] and can be potentially used for NSCLC, even if no data on this kind of application are available so far.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Abu‐Serie et al suggested that higher oxygen intensity of Cu 4 O 3 NPs could activate apoptosis 43 . High ROS production can cause DNA damage that is dependent on various apoptosis‐inducing mechanisms such as, modulation in p53 expression and MMP, and cytochrome C release from mitochondria 50–52 . Furthermore, because GSH lacks S‐glutathiolated protection from caspase‐3, which is activated by proteolytic cleavage, the redox properties of Cu in Cu 4 O 3 NPs may produce reactive hydroxyl radicals that deplete GSH and trigger apoptosis 10,43 .…”
Section: Discussionmentioning
confidence: 99%
“…43 High ROS production can cause DNA damage that is dependent on various apoptosis-inducing mechanisms such as, modulation in p53 expression and MMP, and cytochrome C release from mitochondria. [50][51][52] Furthermore, because GSH lacks S-glutathiolated protection from caspase-3, which is activated by proteolytic cleavage, the redox properties of Cu in Cu 4 O 3 NPs may produce reactive hydroxyl radicals that deplete GSH and trigger apoptosis. 10,43 ROS can also be an attractive target molecules for cancer treatment in addition to being a significant component in the apoptosis intrinsic or extrinsic pathway.…”
Section: Discussionmentioning
confidence: 99%